2009
DOI: 10.1002/ijc.24189
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo study of phloretin‐induced apoptosis in human liver cancer cells involving inhibition of type II glucose transporter

Abstract: Phloretin (Ph), a natural product found in apples and pears with glucose transporter (GLUT) inhibitory activity, exerts antitumor effects. However, little is known about its effects on human liver cancer. The purpose of this study is to test the cytotoxic effects of Ph on HepG2 cells and to identify the underlying molecular pathways. Human hepatocellular carcinoma specimens and HepG2 show a high level of GLUT2 transporter activity in the cell membrane. Real-time PCR and MTT assays demonstrate that Phinduced cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
126
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(131 citation statements)
references
References 48 publications
4
126
0
1
Order By: Relevance
“…Concordantly, our results showed that, in both SW620 and HCT116 cells, PT could not efficiently inhibit cell growth unless the dose was higher than 100 µM. Although previous studies have reported that cytochalasin B could enhance the PT-induced apoptosis of HepG2 cells (21), and that PT can potentiate the anticancer activity of paclitaxel (22), no prior research has focused on synergy involving PT. The results of the present study demonstrated that the antitumor efficacy of ATST could be enhanced at a relatively low dosage through the synergistic action with PT, which suggested the potential interaction of statins with other compounds in the food matrix.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Concordantly, our results showed that, in both SW620 and HCT116 cells, PT could not efficiently inhibit cell growth unless the dose was higher than 100 µM. Although previous studies have reported that cytochalasin B could enhance the PT-induced apoptosis of HepG2 cells (21), and that PT can potentiate the anticancer activity of paclitaxel (22), no prior research has focused on synergy involving PT. The results of the present study demonstrated that the antitumor efficacy of ATST could be enhanced at a relatively low dosage through the synergistic action with PT, which suggested the potential interaction of statins with other compounds in the food matrix.…”
Section: Discussionsupporting
confidence: 79%
“…Phloretin (PT) is one of the most abundant phenolic phytochemicals in apples and apple products. Numerous studies have reported on the antitumor activities of PT, including its ability to suppress cell growth and induce apoptosis in human hepatoma cells, HL-60 human leukemia cells, B16 mouse 4A5 melanoma cells and HT29 human colon cancer cells (18)(19)(20)(21). Both in vitro and in vivo studies have revealed that PT could potentiate the antitumor effects of paclitaxel via the induction of cell apoptosis (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids are well known as antioxidant agents. Phloretin has been reported to inhibit liver cancer [15], breast cancer [16], colon cancer [17], while, its antineoplastic effect on gastric cancer cell is still unclear. In our study we found that 10, 20, 30 μM phloretin significantly inhibit BGC823 gastric cancer cell proliferation by MTT assay.…”
Section: Discussionmentioning
confidence: 99%
“…Our next project will focus on the gene expression profiling of colon cancer cells under this combined treatment. Moreover, we will investigate other Gluts inhibitors such as Fasentin (Wood et al, 2008) and Phloretin (Wu et al, 2009) which were also shown to be effective in reducing cancer cell growth to explore more effective compounds to be utilized as potential anticancer agents for the development of therapeutic strategies.…”
Section: 7037 Overcoming 5-fu Resistant Colon Cells Through the Inhimentioning
confidence: 99%